PIROXICAM-SAVIOUR IN COVID-19 - CHOUDHARI, OMKAR KALIDASRAO; SATYA, DISHA; SONI, PRIYANKA; GUPTA, NAVEEN (International Journal of Current Pharmaceutical Research, 2025)
The pandemic of Coronavirus Disease-2019 (COVID-19) still remains a threat. Its treatment led to the repositioning of many drugs. Piroxicam is one of the non-steroidal anti-inflammatory drugs, which inhibits prostaglandin synthesis and has antiviral activity against NRC-03-nhCoV. Lymphopenia is one of the severity indicators in COVID-19. Cytokine storm is responsible for significant morbidity and mortality in COVID-19. Piroxicam has been shown to induce bone marrow Lymphopoiesis and inhibit Tumour necrosis factor alpha (TNF-α), TNF-γ, actively involved in the cytokine storm.